Intraductal Injection of Lentivirus Vectors for Stably Introducing Genes into Rat Mammary Epithelial Cells in Vivo - Bu, Wen (J Mammary Gland Biol Neoplasia, 2020)
Various retroviral and lentiviral vectors have been used for up-the-teat intraductal injection to deliver markers, oncogenes, and other genes into mammary epithelial cells in mice. These methods along with the large number of genetically engineered mouse lines have greatly helped us learn normal breast development and tumorigenesis. Rats are also valuable models for studying human breast development and cancer. However, genetically engineered rats are still uncommon, and previous reports of intraductal injection of retroviral vectors into rats appear to be inefficient in generating mammary tumors. Here, we report, and describe the method for, stably introducing marker genes and oncogenes into mammary glands in rats using intraductal injection of commonly used lentiviral vectors. This method can infect mammary epithelial cells efficiently, and the infected cells can initiate tumorigenesis, including estrogen receptor-positive and hormone-dependent tumors, which are the most common subtype of human breast cancer but are yet still difficult to model in mice. This technique provides another tool for studying formation, prevention, and treatment of breast cancer, especially estrogen receptor-positive breast cancer.